Competition in the quality of higher education: the impact of student mobility - Gabrielle Demange; Robert Fenge; Silke Uebelmesser (International Tax and Public Finance, 2020)
In the last years, there has been a shift toward more private financing of higher education in many countries. At the same time, student mobility has substantially increased. This paper analyzes in a two-region model the impact of student mobility on region-specific higher education quality with private funding. Individuals decide whether and where to study based on their individual ability and the implemented quality. We show that mobility of students affects educational quality in very different ways depending on the probability of return migration. With full return migration, quality is optimally provided which is in stark contrast to the underprovision result in the case of tax financing. On the contrary, low return migration and thus more competition for students countervail the efficient provision of quality and result in too little differentiated levels or too high symmetric levels. This is in line with the overprovision result with tax financing.
Keywords: H75; I28; R23; 340; Higher education; Migration; Educational quality; Vertical differentiation; Welfare criterion